Тени исчезают в полдень: [роман] / Анатолий Иванов - Иванов Анатолий Степанович (Сибириада, 2022)
Экземпляры: ЦБ (20230529) / Инвентарный номер: 59014 / Цена: 462.00 / Сис.шифр: 84(2=411.2)6 / Авт.знак: И 20 / ГРНТИ: 17.82.31 / ББК: 84(2=411.2)6-44